PENGARUH SUBSTITUSI LABU KUNING (Curcubitamoshcata) TERHADAP KUALITAS BAKSO IKAN NILA (Oreochromisniloticus) - Findya Puspitasari; Rabiatul Adawyah (Fish Scientiae, 2019)
The aims of this study were to determine the level of yellow pumpkin substitution on Nile tilapia fish ball processing to improve the fish ball quality. The treatment used in this study is a different level of substitution (0, 10, 20%) respectively. The Nile tilapia fishball substituted with yellow pumpkin was analyzed in term of water, protein, fat, ash and carbohydrate content. This study uses a completely randomized design (CRD) with three treatments and three replications. The result showed that fish ball with 20% substitution of yellow pumpkin is the best formulation in term of water, protein, fat, ash and carbohydrate content.